Classification of forest vegetation of the national nature park "Karmeliukove Podillya" (Vinnytsya region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Сlassification of the broad-leaved forests vegetation of the National Nature Park "Karmeliukove Podillya" has been developed in accordance with Braun-Blanquet approach based on 147 relevés of forest vegetation collected during 2006–2017 and analysed in Juice software using different methods of cluster analysis. The proposed classification includes three associations, three subassociations, five variants and one community without rank which included in two classes – Carpino-Fagetea sylvaticae and Quercetea pubescentis. The Carpino-Fagetea sylvaticae class is represented by two associations Galeobdolono lutei-Carpinetum and Isopyro thalictroidis-Carpinetum. The first association is represented on the territory of the park by the subassociation sambucetosum nigrae and has a much more pronounced internal differentiation, since it includes three variants that are formed under different anthropogenic impact. The Quercetea pubescentis class is presented in the park with one association Quercetum pubescenti-roboris with newly described subassociation quercetosum petraeae and two variants, characterized by different microclimatic features. According to the results of phytoindictive assessment of the syntaxa it has been established that edaphic factors play a much greater role in their differentiation than climatic ones. Among them, the most influence on the syntaxa differentiation has factors that determine the soils richness – the salt regime of the soil and the content of the accessible forms of nitrogen in soil. 16 species included in the current edition of the Red Data Book of Ukraine were identified as part of the studied vegetation. The most common ones are Sorbus torminalis, Allium ursinum and Viola alba. The studied phytocoenoses of the forest vegetation of the park are typical for the Southeast Podillya, but they have similar features to oak-hornbeam and oak forests of Central and Western Podillya, as well as the Right Bank Prydniprovia. Forest vegetation occupies the most part of the territory of the Karmelіukove Podillya NNP, it is characterized by a rather high floristic and coenotic richness, as well as a significant environmental value, due to the significant participation of rare and endangered species.
Keywords: Braun-Blanquet method, Carpino-Fagetea sylvaticae, phytoindocation, Quercetea pubescentis, Southeast Podillуa, syntaxonomy.